2019
DOI: 10.1080/17483107.2018.1555290
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Analysis of AmpuTees (MAAT 4): classification tree analysis for probability of lower limb prosthesis user functional potential

Abstract: Purpose: To develop a predictive model to inform the probability of lower limb prosthesis users' functional potential for ambulation. Materials and Methods: A retrospective analysis of a database of outcomes for 2770 lower limb prosthesis users was used to inform a classification and regression tree analysis. Gender, age, height, weight, body mass index adjusted for amputation, amputation level, cause of amputation, comorbid health status and functional mobility score [Prosthetic Limb Users Survey of Mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…A recent classification analysis with amputation attributed to cancer, congenital, and trauma collapsed into a singular non-DV group when determining the functional ambulatory status among lower limb prosthesis users 10 . The present study showed no statistical differences between the amputations attributed to cancer and trauma.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…A recent classification analysis with amputation attributed to cancer, congenital, and trauma collapsed into a singular non-DV group when determining the functional ambulatory status among lower limb prosthesis users 10 . The present study showed no statistical differences between the amputations attributed to cancer and trauma.…”
Section: Discussioncontrasting
confidence: 63%
“…Studies have generally shown reduced functional mobility in individuals with DVetiology compared with those with traumatic etiology. [8][9][10] There may not be functional differences between traumatic amputation compared with cancer or congenital etiology. However, the life journey for patients with either cancer or congenital limb deficiency differs substantially from that experienced by patients with either DV or traumatic amputation.…”
Section: What Is Newmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Moreover, previous predictions have estimated outcomes at a single time point, such as 1 year after amputation, rather than the trajectory of functional mobility change over time. [7][8][9][10][11] Particularly during the initial months after the provision of a prosthesis, patient mobility is intended to improve, 12 warranting medical necessity for the prosthesis. Understanding the estimated trajectory of functional mobility change may support prosthesis justification, long-term care planning, and informing realistic expectations of both patients and providers throughout the course of recovery.…”
Section: Introductionmentioning
confidence: 99%